Korean validation of the Motives for Online Gaming Questionnaire: Focusing on its factor structure and incremental validity. (November 2021) - Kim, Bin-Na; Kang, Hyo Shin
Highlights: We validated the K-MOGQ and tried to reconcile mixed findings on factor structure. The K-MOGQ demonstrated a satisfactory reliability. A six-factor solution without the coping factor emerged in a series of EFA and CFAs. The escape and the fantasy motives incrementally predicted increased IGD symptoms. Abstract: Background and aims: Research has suggested that considering gaming motives can be useful in differentiating between heterogenous online game users. This study validated the Korean version of the Motives for Online Gaming Questionnaire (K-MOGQ) and attempted to reconcile the mixed findings on its factor structure. We also examined the incremental validity of the K-MOGQ beyond the personality variables implicated in Internet gaming disorder (IGD). Methods: After informed consent, six hundred and forty-one Korean online game users (mean age = 21.49 years) completed a survey package including the K-MOGQ. After exploratory factor analysis (EFA) was conducted, all existing models were compared using confirmatory factor analysis (CFA). A hierarchical regression analysis was conducted to demonstrate the incremental variance explained by gaming motives. Results: The K-MOGQ demonstrated a satisfactory reliability. The EFA and CFA revealed a six-factor (fantasy, escape, skill development, competition, recreation, and social motives) solution in which the coping factor disappeared from the original seven-factor structure. In addition, the escape and fantasy motives significantly predicted increased IGD symptoms even when introversion, neuroticism, and impulsivity were controlled for. Discussion and conclusions: Our results indicate that the K-MOGQ possesses good psychometric properties for measuring the motivational basis of online gaming in Korean-speaking populations. Furthermore, escape and fantasy factors emerged as the most salient motives for IGD symptoms. More research is required to clarify whether a Western–Eastern distinction applies to the factor structure of the MOGQ.